Cytogenetic Study in a Mutant of Triatoma infestans (Hemiptera: Reduviidae) Carrying a Spontaneous Autosomal Fusion and an Extra Chromosome - Poggio, María Georgina (2012)
Triatoma infestans (2n = 20 A + XY, male) is a blood-sucking bug and the most important vector of Chagas disease. Cytogenetic analysis of one population from Argentina has revealed the presence of one naturally occurring heterozygous for an autosomal fusion. The fusion heterozygote (2n = 19 A + 1 B + XY) presented an autosomal trivalent eight bivalents, the X and Y sex univalents, and a minute neo-extra or B chromosome at meiosis I. The autosomal trivalent divided equationally at first anaphase. At meiosis II, cells had eight autosomes, X and Y sex chromosomes, and a pseudo-trivalent composed by three chromatids of different sized (a triple chromatid). At metaphase II, the orientation of the triple chromatid led to a reductional segregation, that is, the largest chromatid migrates to one pole while the other two to the other one. The meiotic behaviour of this new chromosome complement was highly regular. The presence of an extra or B chromosome did not affect the segregation of both autosomes and sex chromosomes during both meiotic divisions. All cells analysed would be balanced, since there were no macrospermatids or microspermatids. Taking into account our results we propose that the B-chromosome was originated as a product of the autosomal fusion. Many authors propose that karyotype evolution in Heteroptera has proceeded mainly by autosomal fusions and sex chromosome fragmentations. Particularly in Triatominae, it has been proposed that karyotype evolution from the ancestral number 2n = 20 A + XY has occurred through autosomal fusions and an X chromosome fragmentation. The facts that an autosomal fusion has been found in natural population of Triatoma infestans, and it shows a regular meiotic behaviour seem to support the suggested hypothesis.